Influence of behavior and maternal perception on their children’s eating and nutritional status - Kathleen Jellmayer; Aline de Piano Ganen; Marle Alvarenga (O Mundo da Saúde, 2017)
Mothers carry a major responsibility for nutrition and feeding behavior during childhood. The present study aimed to analyze the maternal attitude and perception of the mealtimes and nutritional status of their children. A non-probabilistic sample of 116 mothers and their respective children who go to the Basic Health Units of the City of Sao Paulo, were invited to respond to a Parent Mealtime Action Scale (PMAS) and the Child Feeding Questionnaire (CFQ). The age, income, education and nutritional status of mothers and their children were assessed, and the associations between these characteristics and the PMAS and CFQ scores were examined using linear regression. The correlations between PMAS and CFQ were analyzed by the Spearman test and the nutritional status correlations between mothers and their children, by the Pearson’s chi-square. It was found that 71.5% of the mothers and 57.7% of the children were either overweight or obese. The most common positive maternal attitudes according to the PMAS were: daily offer of fruits and vegetables, limits on sweets, and positive persuasion. The negative attitudes were sweet-eating role models, use of rewards and providing many food options. Among the CFQ factors, the most frequent were: perceived responsibility toward their children’s food intake, monitoring by mothers of healthy food consumption, junk food restrictions, and exerting pressure to eat. There was a moderate correlation between the nutritional status of the mother and child. It was concluded that the attitudes and perceptions of mothers regarding their children’s nutrition vary according to their own nutritional status, as well as the child’s.